Bioinspired Lipase Immobilized Membrane for Improving Hesperidin Lipophilization - Shanxiu Ming; Shuyi Li; Zhe Chen; Xujun Chen; Feifei Wang; Shaonan Deng; Krystian Marszałek; Zhenzhou Zhu; Wenxiang Zhang; Francisco J. Barba (Antioxidants, 2022)
Lipophilization is a promising way to improve the bioavailability of flavonoids. However, the traditional enzymatic esterification methods are time-consuming, and present low yields and purity. Herein, a novel membrane-based lipophilization technology—bioinspired lipase immobilized membranes (BLIMs), including CAL-B@PES, CAL-B@PDA/PES and GA/CAL-B@PDA/PES— were fabricated to improve the antioxidant flavanone glycoside hesperidin lipophilization. Via reverse filtration, PDA coating and GA crosslinking, Candida antarctica lipase B (CAL-B) was stably immobilized on membrane to fabricate BLIMs. Among the three BLIMs, GA/CAL-B@PDA/PES had the greatest enzyme activity and enzyme loading, the strongest tolerance of changes in external environmental conditions (temperatures, pH, heating time, storage time and numbers of cycles) and the highest hesperidin esterification efficiency. Moreover, the optimal operating condition for GA/CAL-B@PDA/PES fabrication was the CAL-B concentration of 0.36 mg/mL, operation pressure of 2 bar, GA concentration of 5% and crosslinking time of 1 h. Afterwards, the hesperidin esterification process did not affect the micromorphology of BLIM, but clearly improved the BLIM permeability and esterified product efficiency. The present study reveals the fabrication mechanism of BLIMs and offers insights into the optimizing strategy that governs the membrane-based lipophilization technology process.